An enhancement of the Boyer-Moore Algorithm applied in braille translation - Sarah B. Borja and Raffy C. Solayao. 4 0 16; 5 (2016)
u
Thesis: (BSCS major in Computer Science) - Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2